An Observational Study of the Morning and Evening Behavior of Individuals With and Without Attention-Deficit/Hyperactivity Disorder. Issue 9 (July 2022) - Fabiano, Gregory A.; Tower, Devon; Valente, Matthew; Rejman, Emilea; Rodriguez, Zulema
As individuals with ADHD move to young adulthood, the morning and evening times become of increased importance. Sixty individuals were enrolled in a 14-day study (30 with ADHD and 30 did not have ADHD). Participants provided self-reports of ADHD symptoms and impairment using ecological momentary assessments administered each morning and each evening. Participants also identified a collateral who could provide daily ratings of the participant during the same time. Driving data were also passively collected. Results indicated differences in self and collateral ratings of ADHD symptoms and impairment, with greater symptom endorsement and reports of impairment for the individuals with ADHD. Self-report indicated greater endorsement in the evening, relative to the morning, for individuals with ADHD. Collateral report did not interact with time of day. Passive evaluation of driving performance was not significantly different. Results indicate young adult ADHD symptoms and impairment can be reliably assessed in the morning/evening. Public Health Significance: Evidence of ADHD symptoms and impairments were documented in the morning and evening hours for individuals diagnosed with ADHD. These results illustrate additional areas in need of attention in the refinement of treatments for adults with ADHD.